PERAN DAN TANTANGAN TEKNOLOGI DIGITAL DALAM MENINGKATKAN KUALITAS PEMBELAJARAN DI SMAN 8 TANGERANG SELATAN - Ramadhani, Aura Nafisha; Aulia , Rahma; Louiz , Barent; Mulyadi, Mulyadi; Subakdi, Subakdi; Halim, Abdul; Mana, Ronald; Bramantyo , Andreas (Inspirasi: Jurnal Pengabdian Masyarakat, 2024)
The development of technology today brings many innovations, especially in learning which continues to change with the times. Technology is often utilized in the learning process, which must be well planned to provide the best service to students. The utilization of learning media in accordance with the times is the key to achieving learning objectives. Therefore, the purpose of implementing this community service activity through socialization/counseling on the importance of the role of technology in the learning process at school and the challenges in using technology itself is so that students know and understand that technological innovation today has many positive impacts that can help and facilitate the learning process at school, but in addition there are also negative impacts in the form of challenges and problems faced from the use of technology. Community service activities are carried out through counseling/socialization by providing information through the methods of exposure, lectures, questions and answers, and playing game. The reason this method is used is to encourage active learning and effective interaction. Learning through lectures, questions and answers, and game will provide opportunities for students to learn not only to understand the material theoretically but to actively participate in discussions, apply knowledge in practical situations, and develop social and collaboration skills.